Antiretroviral manufacturers and the challenge of universal access to drugs through the Brazilian National STD/AIDS Program As empresas produtoras de anti-retrovirais e o desafio do acesso universal aos medicamentos do Programa Nacional de DST e AIDS - Regina Ferro do Lago; Nilson do Rosário Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
This article describes the antiretroviral (ARV) manufacturing market in Brazil and contextualizes the challenges for the public policy of supplying ARVs through the National STD/AIDS Program. Increasing expenditure on these drugs is the main source of uncertainty for the policy's future. Brazil's domestic scenario is one of growing external dependence, both for the finished drugs and the active ingredients. Experience in the National Program has shown that it is the state's role to provide public goods, which presupposes ensuring mutual compatibility between company interests and social interests. This balance is currently at stake in Brazil, since structural changes in the market have raised challenges for the National Program's sustainability, requiring new public policy instruments in defense of the collective interest. The article drew on a literature review, using bibliographic indexing sources, systematic organization of primary data, government publications, relevant legislation, research reports, and articles recommended by experts from the field. O artigo descreve as características do mercado produtor de anti-retrovirais no Brasil e situa os desafios para a política pública de provisão de medicamentos no Programa Nacional de DST e AIDS (PN-DST/AIDS). A elevação expressiva das despesas com esses medicamentos é a principal fonte de incerteza sobre a política. O cenário nacional é de crescente dependência externa, tanto no segmento de medicamentos quanto no de princípios ativos. A experiência do PN-DST/AIDS demonstrou que cabe ao Estado nacional a provisão de bens públicos, o que pressupõe a compatibilização entre interesses empresariais e sociais. Esse equilíbrio está sendo desafiado no Brasil visto que as mudanças estruturais no mercado trouxeram desafios à sustentabilidade do programa, exigindo novos instrumentos de política pública em defesa do interesse coletivo. Para a confecção do artigo empreendeu-se revisão da literatura usando-se fontes de indexação bibliográfica, sistematização de dados primários, publicações de órgãos públicos, legislações pertinentes, relatórios de pesquisa e artigos indicados por especialistas da área.